Lost Letters: Using the Lost-letter Technique to Teach Social Research Methods. (October 2018) - Reid, Matt
Over 50 years ago, Stanley Milgram and colleagues published a short article detailing an unobtrusive experimental design they called the lost-letter technique. The technique involves placing stamped, unmailed letters in a community and using the relative rate of return to infer local attitudes toward political issues and social groups. Furthermore, the technique is simple and inexpensive enough to replicate in an introductory-level social science course as a means to familiarize students with social research methodology. This activity utilizes active learning with student-centered pedagogy, and this paper details the procedure, best practices, and student feedback. Students enjoy having a personal stake in the project and find they better understand social research through this active learning project. Instructors are encouraged to consider adopting the technique in their courses.